Sports Participation, Social Networks, and Sexual Violence Perpetration. Issue 1 (January 2023) - Nickodem, Kyle K.; Basile, Kathleen C.; Espelage, Dorothy L.; Leemis, Ruth W.; Ingram, Katherine M.; Barbero, Colleen
Adolescent sexual violence (SV), which includes non-contact verbal sexual harassment (SH) and forced sexual contact (FSC), is a significant public health problem with long-term impacts on health and well-being. Understanding how sports participation is linked to SV can inform prevention efforts; however, the current literature is unclear about the nature of this association. Using data from 20 high schools, we investigate whether athletes in certain sports are at higher risk of SH and FSC perpetration than either other athletes or sports non-participants, and whether the risk is moderated by gender, dismissiveness of SV, or substance use intentions. We also utilize social network data to explore the role of relationships with peers and trusted adults to attenuate SH and FSC perpetration. Second, we incorporate characteristics of friends to further examine the role and composition of peer groups in the association between sports participation and perpetration of SH and FSC. Findings revealed a bivariate association between sport contact level and SH perpetration, but not FSC, and the association disappeared after adjusting for other covariates. Most prominently, dismissiveness of SV, intentions to use substances, and prior perpetration had the strongest association with perpetration regardless of sport contact level. Results also provided some support for the influence of peers and trusted adults in the sports context. Notably, the percentage of friends who perpetrated FSC and the percentage of friends who play a low-contact sport were positively associated with FSC perpetration, and the percentage of friends who play a high-contact sport was positively associated with SH perpetration. The paper concludes with a discussion of the sports context as an important venue for comprehensive prevention efforts, including a focus on changing norms around adolescent SV and substance use.